Splicing defect of StDRO2 intron 1 promotes potato root growth by disturbing auxin transport to adapt to drought stress - Jianping Zhao; Baolin Yao; Ziai Peng; Xinyue Yang; Kuixiu Li; Xiaoyan Zhang; Haiyan Zhu; Xuan Zhou; Meixian Wang; Lihui Jiang; Xie He; Yan Liang; et al. (Horticultural Plant Journal)
The formation of root system architecture (RSA) plays a crucial role in plant growth. OsDRO1 is known to have a function in controlling RSA in rice, however, the role of potato StDRO2, a homolog of rice OsDRO1, in root growth remains unclear. In this study, we obtained potato dro2 mutant lines by Clustered Regularly Interspaced Short Palindromic Repeats-CRISPR-Associated 9 (CRISPR/Cas9)-mediated genome editing system. The mutant lines were generated from a splicing defect of the StDRO2 intron 1, which causes a nonsense mutation in StDRO2. Furthermore, the secondary structure of StDRO2 mRNA analyzed with RNAfold WebServer was altered in the dro2 mutant. Mutation of StDRO2 conveys potato adaptation through changing the RSA via alteration of auxin transport under drought stress. The potato dro2 lines showed higher plant height, longer root length, smaller root growth angle and increased tuber weight than the wild-type. The alteration of RSA was associated with a disturbance of IAA distribution in the dro2 mutant, and the levels of StPIN7 and StPIN10 detected by using real-time PCR were up-regulated in the roots of potato dro2 lines grown under drought stress. Moreover, the microRNAs (miRNAs) PmiREN024536 and PmiREN024486 targeted the StDRO2 gene, and auxin positively and negatively regulated the expression of StDRO2 and the miRNAs PmiREN024536 and PmiREN024486, respectively, in the potato roots. Our data shows that a regulatory network involving auxin, StDRO2, PmiREN024536 and PmiREN024486 can control RSA to convey potato fitness under drought stress.